Dental Emergencies and Coronavirus Disease-2019: Scoping Review of the Literature and Single Centre Experience - Agostino Guida; Annamaria Carotenuto; Vladimiro Lanza; Francesco Antonucci; Paola Salerno; Dario Marasca; Umberto Esposito; Maurizio Gargiulo (MDPI AG, 2022)
Understanding the impact of the COVID-19 pandemic on dental emergencies. A systematic review of the literature (PubMed/Scopus) searching for articles on COVID-19 and dental abscess and a retrospective cohort study with quantitative/qualitative data analysis of our hospital E.R. patients admitted for cervico-facial abscess of dental origin were performed. Thirteen studies could be included in the review, concerning characteristics/management of patients with dental emergencies in hospitals/private practices, generally with poor evidence. For the retrospective analysis, 232 consecutive patients were included (100 study vs. 132 control). The prevalence of dental emergencies (abscess) and relative complications (mediastinitis, exitus) increased. Dental care availability was limited, with strong heterogeneity amongst regions/nations. At-risk (aerosol-generating) procedures were generally avoided, and hospitalization length reduced. Comorbidity patients and males seem less likely to restore regular dentist attendance during the post-lockdown pandemic. Despite the poor scientific evidence, COVID-19 seems to have impacted dental emergencies through limited routine dental care availability and influence on physicians' and patients' behaviour.